Nitric oxide partitioning into mitochondrial membranes and the control of respiration at cytochrome c oxidase - Shiva, Sruti (The National Academy of Sciences, 2001)
An emerging and important site of action for nitric oxide (NO) within cells is the mitochondrial inner membrane, where NO binds to and inhibits members of the electron transport chain, complex III and cytochrome c oxidase. Although it is known that inhibition of cytochrome c oxidase by NO is competitive with O(2), the mechanisms that underlie this phenomenon remain unclear, and the impact of both NO and O(2) partitioning into biological membranes has not been considered. These properties are particularly interesting because physiological O(2) tensions can vary widely, with NO having a greater inhibitory effect at low O(2) tensions (<20 μM). In this study, we present evidence for a consumption of NO in mitochondrial membranes in the absence of substrate, in a nonsaturable process that is O(2) dependent. This consumption modulates inhibition of cytochrome c oxidase by NO and is enhanced by the addition of exogenous membranes. From these data, it is evident that the partition of NO into mitochondrial membranes has a major impact on the ability of NO to control mitochondrial respiration. The implications of this conclusion are discussed in the context of mitochondrial lipid:protein ratios and the importance of NO as a regulator of respiration in pathophysiology.